The Effect of Early Spironolactone Administration on 2-Year Acute Graft Rejection in Cardiac Transplant Patients - Dragos-Florin Baba; Alina Danilesco; Horatiu Suciu; Calin Avram; Marius Mihai Harpa; Mircea Stoian; Diana-Andreea Moldovan; Laurentiu Huma; Gabriel Rusu; Tunde Pal; Adina Stoian; Anca-Ileana Sin (Biomedicines)
Background: The objective of our study was to investigate the impact of mineralocorticoid receptor antagonists (MRAs), such as spironolactone, administrated early after cardiac transplantation on the occurrence of acute graft rejection (AGR) in the first 2 years post-transplant. Methods: This retrospective research was conducted in the Emergency Institute for Cardiovascular Diseases and Transplantation of Targu Mures, Romania. After applying the inclusion criteria, between January 2011 and December 2023, 36 patients fit the study design. Using Cox proportional hazards regression and Kaplan–Meier curves, we determined the time-to-event distribution, for which the first episode of AGR was considered an event, with a significance threshold of 0.05. Results: The 1-year rate of AGR was 38.9% and was 47.2% at 2 years, with a 2-year mortality of 11.1%. The interpretation of the Cox regression indicated that early initiation of spironolactone represents a protective factor against the 2-year AGR (HR: 0.263; 95%CI: 0.076–0.922; p = 0.037 by the log-rank test). Conclusions: These results might suggest a possible benefit of the early administration of spironolactone after a heart transplant, but further prospective studies need to be performed for the validation of our findings.